Indication of new climatic proxy by loess iodine variation. (1st January 2021) - Fan, Yukun; Zhou, Weijian; Hou, Xiaolin; Kong, Xianghui; Chen, Ning; Burr, George S.
Abstract: Paleoclimate change research routinely takes advantage of a variety of climate proxies. Each proxy responds to climate in its own way and a combination of proxies offers the best means of understanding past climate at a given site. Here we present iodine variation patterns in one classical loess-paleosol sequence in the Chinese Loess Plateau to develop a new proxy that responds to climate-induced changes in the source availability, transport dynamics and depositional environment of iodine. Our iodine variation provides a continuous record for the past ∼260 kyr, and is highly correlated with traditional climate proxies, including magnetic susceptibility, mean grain size and organic matter content. We attributed the variations of the iodine record to past climate changes particularly in aspects of coupled air-sea circulation, transport dynamics, and depositional retention on the Chinese Loess Plateau. We propose that geochemistry of iodine variation provides a new tool for assessing paleoclimate changes in aspects of large-scale air-sea circulation mechanism, global iodine transport dynamics, and depositional environment as particular enrichment factors in the Chinese Loess Plateau. Graphical abstract: Image 1 Highlights: The first iodine record from a loess-paleosol sequence was reconstructed. Iodine content varies with a strong correlation with traditional climate proxies. Climate affected sea-land transport, deposit and retention of I on loess plateau.